If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -6 = 5x Reorder the terms: -6 + 7x = 5x Solving -6 + 7x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -6 + 7x + -5x = 5x + -5x Combine like terms: 7x + -5x = 2x -6 + 2x = 5x + -5x Combine like terms: 5x + -5x = 0 -6 + 2x = 0 Add '6' to each side of the equation. -6 + 6 + 2x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = 0 + 6 2x = 0 + 6 Combine like terms: 0 + 6 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| x^2-15x=0 | | -x^2+5x=0 | | 7x-40=2x | | f+f-5=95 | | 4(5-3x)=2(5x-4)+2(3-x) | | x^2+5x=0 | | e+e+6=74 | | 3(n-1)=9 | | -s^2-15s=0 | | -15s^2-15s=0 | | 6x-26=-14 | | s(t)=10+18t+16t^2 | | -a^2+9a=0 | | -a^2=9a | | X-2y=12 | | a^2-7a=0 | | 5x-33=-13 | | s^2-6s=0 | | 8x-24=40 | | b^2-3b=0 | | 8x-24=4-0 | | -b^2+11b=0 | | 6x+39=-21 | | 4(5x+1)+3(1-7x)=x | | 9x=8x+1x | | 9s-12+25=21 | | 9z-18=36+9z | | 7w-15=-33+5w | | 4r-11+5r=25 | | x-23=8x+5 | | 50-12c=10-8c | | 2m-54=4m |